Implementation of a Simple Lifestyle in Preventing Hedonism and Consumptive Behavior Among Students at The Nurul Muchlishin Islamic Boarding School - Faridatul Jamilah; Abd. Warits (Interpersonal: Jurnal Bimbingan Konseling Islam, 2025)
This study will explore several issues as follows: first, describing the simple lifestyle at the Nurul Muchlishin Islamic boarding school; second, explaining the implementation of a simple lifestyle at the Nurul Muchlishin Islamic boarding school; third, describing the positive implications of implementing a simple lifestyle in preventing hedonism and consumptive behavior among students at the Nurul Muchlishin Islamic boarding school. The research method used is a qualitative descriptive approach with field research (qualitative research). The data collection techniques used included observation, interviews, and documentation. This study produced the following findings: first, students at the Nurul Muchlishin Islamic boarding school were trained to distinguish between needs and wants through the habit of living simply. Second, the implementation of a simple lifestyle has proven effective in curbing luxurious and consumptive lifestyles through restrictions on clothing, bans on online shopping and buying food from outside, and wise financial management. Third, the implementation of a simple lifestyle has a positive impact on the character of students, encouraging awareness of needs, fostering responsibility, independence, and consistency in living according to the values and principles of the boarding school.